A mitochondria-targeted nano-platform for pancreatic cancer therapy - Tan, Xiaoke; Zhu, Xin; Xu, Duanjie; Shi, Yanmei; Wang, Zhenzhen; Cao, Mingzhuo; Hu, Kai; Zhao, Lingzhou; Zhao, Junwei; Miao, Mingsan; Zeng, Huahui; Wu, Xiangxiang (Frontiers in Chemistry, 2022)
Liposome is a conventional drug delivery system which has been widely used in the pharmacy field. However, its applications are greatly restricted in clinical practice by the disadvantages of cholesterol and nonselective distribution. Herein, a novel platform for the anti-tumor drug delivery was developed by incorporating an amphiphilic stachydrine-octadecane conjugate (SS) as the mitochondria-targeting molecule onto the triptolide-liposome surfaces (SS-TP LPs). The polyethylene glycol (PEG) and the suitable particle size (about 130 nm) of liposomes facilitated their stabilities, the long half-life in blood and the escape from the rapid elimination. The SS-TP LPs were internalized and accumulated into the mitochondria of cancer cells in a time-dependent manner, followed by triggering permeabilization of the mitochondrial outer membrane by inhibiting Bcl-2, and then further caused greater cancer cell death via releasing cytochrome C, and initiating a cascade of caspase 3 reactions. In the Pan02 tumor-bearing mice, the SS-TP LPs showed significant efficacy in inhibiting tumor growth and reducing tumor size, but synchronously exhibited specific mitochondria-targeting and much lower subacute toxicity, compared with the free TP and TP LPs. Our study suggest that SS-TP LPs can be a promising anticancer drug delivery system for the mitochondria-targeted therapy in pancreatic cancer.